Module Development through Project-Based Learning to Enhance Students’ Creative Thinking - Praptama, Sandhi Setya; Purwaningsih, Endang; Taufiq, Ahmad; Setiyoaji, Wahyudha Tri (Universitas Muhammadiyah Makassar, 2023)
In implementing the project-based learning model, students are expected to improve their creative thinking. This research aims to develop a module through project-based learning to improve the creative thinking skills of vocational students. Employing a research and development design, the research involves a 4-D model with four stages, namely defining, designing, developing, and disseminating. Respondents in this study were teachers and students at SMKN 1 Grati, Pasuruan Regency, totaling 13 people. The research was carried out during the period August 1 – September 15, 2021. The results showed that the average value of the validation results for PjBL-based modules was 88.3% (very valid), and lesson plans were 80.3 (valid). Then, the average percentage of teachers’ responses to the modules that have been developed was 85% (very practical,) and of students’ responses was 78% (practical). Therefore, it can be concluded that the PjBL-based learning module developed in the research can be categorized as valid and practical.